2017
DOI: 10.7205/milmed-d-16-00154
|View full text |Cite
|
Sign up to set email alerts
|

Professional Stress and Burnout in U.S. Military Medical Personnel Deployed to Afghanistan

Abstract: Although a cross-sectional survey, results provide three specific directions for reducing burnout in deployed medical staff. By emphasizing self-care, team care, and health-promoting leadership, policy makers, researchers, and leaders can address factors that influence burnout in this, and other occupational contexts. In addition, the constructs of team care and leadership offer novel contributions to the study of burnout in medical personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 33 publications
4
60
0
2
Order By: Relevance
“…In our investigation, we found statistically significant differences between anxiety, measured on the BAI questionnaire, and all three subscales of burnout. Correlation between anxiety and burnout has shown that the level of anxiety was in connection of increase the emotional exhaustion and depersonalization and decrease of personal accomplishment, which is consistent with the results of other studies (19).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our investigation, we found statistically significant differences between anxiety, measured on the BAI questionnaire, and all three subscales of burnout. Correlation between anxiety and burnout has shown that the level of anxiety was in connection of increase the emotional exhaustion and depersonalization and decrease of personal accomplishment, which is consistent with the results of other studies (19).…”
Section: Discussionsupporting
confidence: 91%
“…Anxiety is defined as the feeling of floating fear, embarrassment and uneasiness. It is a normal reaction to a stressful situation, however, if it lasts longer and if the person cannot control it, it goes into anxiety disorder (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domain-speci c leadership has been studied in a variety of contexts from family-supportive supervisory behaviors (38) to safety leadership (39,40). In the military, this concept has included combat operational stress control leadership (41), sleep leadership (42,43), and health-promoting leadership (41,44,45). This research identi es speci c areas that leaders can focus on to support relevant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies focused on military medical workers [4,6,7]. The prevalence of job burnout and the risk factors among military personnel in combat troops are still unclear.…”
Section: Introductionmentioning
confidence: 99%